NCATS Inxight Drugs: a comprehensive and curated portal for translational research. Issue Volume 50:Issue D1(2022) (14th October 2021) - Siramshetty, Vishal B; Grishagin, Ivan; Nguyễn, Ðắc-Trung; Peryea, Tyler; Skovpen, Yulia; Stroganov, Oleg; Katzel, Daniel; Sheils, Timothy; Jadhav, Ajit; Mathé, Ewy A; Southall, Noel T
Abstract: The United States has a complex regulatory scheme for marketing drugs. Understanding drug regulatory status is a daunting task that requires integrating data from many sources from the United States Food and Drug Administration (FDA), US government publications, and other processes related to drug development. At NCATS, we created Inxight Drugs (https://drugs.ncats.io ), a web resource that attempts to address this challenge in a systematic manner. NCATS Inxight Drugs incorporates and unifies a wealth of data, including those supplied by the FDA and from independent public sources. The database offers a substantial amount of manually curated literature data unavailable from other sources. Currently, the database contains 125 036 product ingredients, including 2566 US approved drugs, 6242 marketed drugs, and 9684 investigational drugs. All substances are rigorously defined according to the ISO 11238 standard to comply with existing regulatory standards for unique drug substance identification. A special emphasis was placed on capturing manually curated and referenced data on treatment modalities and semantic relationships between substances. A supplementary resource 'Novel FDA Drug Approvals' features regulatory details of newly approved FDA drugs. The database is regularly updated using NCATS Stitcher data integration tool that automates data aggregation and supports full data access through a RESTful API.